Informasi Kemiskinan Rekayasa Perangkat Lunak - Habibie Pratama A.N.; Kelvin K. Saputra; Egy Patriasta (CV. Multi Kreasi Media, 2023)
With regards to executing different destitution mitigation programs, data about who the poor are and where they are is vital. In Indonesia, information sources on destitution are accessible from different sources. Be that as it may, the authority source utilized by the public authority is neediness information from the Focal Department of Measurements (BPS). Destitution information obtained from BPS is much of the time the reason for executing neediness lightening programs by government organizations. In view of the exploration that has been finished, the most common way of deciding destitution information designs involving the Information Disclosure in Data set (KDD) technique and utilizing PPLS information from the Focal Measurements Organization produces seven data designs. The seven data designs are the consequence of bunching/gathering destitution information by locale and neediness level in light of destitution pointers. The designing system of destitution information data programming was assembled utilizing the Quick Application Improvement (RAD) strategy to address the officials for neediness information data.